Future Directions in Quantitative SPECT-CT Evaluation of Cardiac Transthyretin Amyloidosis: Correlation with Clinical and Morphological Parameters - Mirela Gherghe; Mario-Demian Mutuleanu; Tatiana Lucia Suta; Liliana Micu; Adina Elena Stanciu; Sinziana-Octavia Ionescu; Ciprian Cirimbei; Diana Loreta Paun; Andreea Jercan; Sorina Nicoleta Badelita; Daniel Coriu (Diagnostics)
Background: ATTRv and ATTRwt cardiac amyloidosis (CA) are underrecognized causes of heart failure with preserved left ventricular ejection fraction. The diagnosis of CA remains challenging due to low diagnostic suspicion and clinical overlap with more common diseases. The aim of this study was to use [99mTc]-PYP SPECT-CT to perform a volumetric evaluation of bone scintigraphy to overcome the limitations of current practices. Methods: A monocentric prospective study was conducted to evaluate a lot of 22 patients with a mean age of 52.86 ± 13.80 years, diagnosed with hereditary cardiac transthyretin amyloidosis (ATTR). Results: Correlations between the quantitative SPECT-CT, clinical data, and morphological parameters were performed, demonstrating moderate to strong correlation of SUVmaxMyocardium/SUVmaxBone to both ECG low voltage and EchoGLS, SUVmaxMyocardium/SUVmaxLiver to myocardial gadolinium kinetics with T1 mapping MRI, diastolic disfunction, sensory–motor polyneuropathy, and EchoGLS, SUVmaxMyocardium/SUVmeanBone with diastolic disfunction and sensory–motor polyneuropathy, as well as SUVmaxMyocardium/SUVmaxSoft tissue to S II, respectively. Conclusions: The moderate to strong correlations among advanced quantitative SPECT-CT metrics and clinical and paraclinical data create the premises to use these parameters for early diagnosis of cardiac ATTR. Further multicentric studies in a larger patient population are needed to validate the newly identified quantitative SPECT-CT parameters.